Writing anxiety among international students in a Thai university - Jebamani Anthoney; Jeffrey Dawala Wilang (International Journal of Evaluation and Research in Education (IJERE), 2023)
Literature on writing anxiety among undergraduate students in international universities situated in English as a foreign language context remains scarce. In this study, a survey questionnaire was distributed to know the writing anxiety level of students and anxiety level differences based on nationality and locality. A total of 138 students participated using convenience sampling. Afterward, five students, based on their writing anxiety level, were purposely chosen to attend two sorting activities of statements regarding the change in their writing anxiety. Then, individual semi-structured interviews were conducted to know the factors of writing anxiety change. Descriptive results from the survey have shown that students in an international university experienced high anxiety in specific situations in writing. Also, varying writing anxiety levels were found based on nationality and locality. Findings from the sorting activity indicated that some writing anxiety-provoking situations have changed over a 2-week time frame due to some factors. Some implications for teaching were recommended to reduce writing anxiety in the classroom.